2022
DOI: 10.1002/cam4.4933
|View full text |Cite
|
Sign up to set email alerts
|

Integrative metabolomics and transcriptomics analysis reveals novel therapeutic vulnerabilities in lung cancer

Abstract: Background Non‐small cell lung cancer (NSCLC) comprises the majority (~85%) of all lung tumors, with lung adenocarcinoma (LUAD) and squamous cell carcinoma (LUSC) being the most frequently diagnosed histological subtypes. Multi‐modal omics profiling has been carried out in NSCLC, but no studies have yet reported a unique metabolite‐related gene signature and altered metabolic pathways associated with LUAD and LUSC. Methods We integrated transcriptomics and metabolomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The integration of metabolomic and transcriptomics could reveal consistent metabolic alterations at both the metabolites and mRNA levels, providing insight into molecular mechanisms and targeted therapies of lung cancer. Current integrative studies have identified metabolite-related gene signatures and key metabolic pathways aberrantly regulated in lung adenocarcinoma and squamous cell carcinoma [15]. Nevertheless, none of these studies have focused on GGO-associated lung cancer.…”
Section: Ivyspringmentioning
confidence: 99%
“…The integration of metabolomic and transcriptomics could reveal consistent metabolic alterations at both the metabolites and mRNA levels, providing insight into molecular mechanisms and targeted therapies of lung cancer. Current integrative studies have identified metabolite-related gene signatures and key metabolic pathways aberrantly regulated in lung adenocarcinoma and squamous cell carcinoma [15]. Nevertheless, none of these studies have focused on GGO-associated lung cancer.…”
Section: Ivyspringmentioning
confidence: 99%
“…A study using RNA-Seq transcriptomics and Mass-Spectrometry metabolomics in LUAD derived a 28-gene signature with prognosis capability. Also, they led to the identification of a novel lung cancer drug, AZD-6482, a PI3Kβ inhibitor [ 130 ].…”
Section: Multiomics Insight Into Clinical Diseasementioning
confidence: 99%
“…A study using RNA-Seq transcriptomics and Mass-Spectrometry metabolomics in LUAD derived a 28-gene signature with prognosis capability and also led to the identification of a novel lung cancer drug, AZD-6482, a PI3Kβ inhibitor. [95] COPD is a risk factor for lung cancer and Sandri et al report multi-omic analysis of the lung stroma in patients with COPD who developed cancer compared to those who did not, testing the hypothesis that lung stroma in COPD has upregulated molecular mechanisms that support carcinogenesis [96]. Predictive variables for cancer compared to adjacent stroma, were mainly represented in the transcriptomic data, whereas predictive variables associated with adjacent tissue, compared to controls.…”
Section: Lung Cancermentioning
confidence: 99%